Discovering Syntax : Clause Structures of English, German and Romance. - Emonds, Joseph E. (Studies in Generative Grammar, No. 93., 2008)
The essays in this volume, dating from 1991 onwards, focus on highly characteristic constructions of English, Romance languages, and German. Among clause-internal structures, the most puzzling are English double objects, particle constructions, and non-finite complementation (infinitives, participles and gerunds). Separate chapters in Part I offer relatively complete analyses of each. These analyses are integrated into the framework of Emonds (2000), wherein a simplified subcategorization theory fully expresses complement selection. Principal results of that framework constitute the initial es.